MySchool Application as a Computer-mediated Communication for Parents, School, and Teachers - Bobby Yocbahawie; Naftali Yudhistira; Mugiatno Sumbodo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
School is a very important place for every individual and also the primary center of a smartnation generation where the teaching and learning process is carried out continuously everyday. In the teaching and learning process, communication between parents and schools plays avery important role because students' academic success cannot be separated from the supportof their parents, currently parents and schools usually create WhatsApp Groups (WAGs) toestablish communication whose purpose is to find out about activities students in school suchas: attendance, student grades, exam schedule, important announcements, and others.Moreover, the Covid-19 Pandemic adds to the series of problems that must be resolved andimmediately sought for solutions together. For this reason, a system is needed to overcomethese problems through the use of information technology in the communication processbetween parents and schools. MySchool application aims to solve communication problemsbetween parents, teachers, and schools, besides this application also aims to support the schooladministration system in such as tuition fees, information on school activities, importantannouncements, and others. This application is also a series of solutions for the teaching andlearning processes of school activities during the Covid-19 pandemic and by optimizing it canconvert all activities to be completely digital ones. The feedbacks were very positive likehaving mobile app as a mean of communication at school provides effective relationshipbetween parents and the school.